Pengaruh Model Learning Cycle 5E Berbasis Eksperimen Terhadap Kemampuan Berpikir Kritis Fisika Peserta Didik Kelas XI SMAN 1 Gerung - I'in Senja Septiana; Ahmad Harjono; Hikmawati Hikmawati (Department of Physics Education, Universitas Mataram, 2018)
This research aims to determine the effect of experimental based learning cycle 5E model to the critical thinking ability of physics students class XI SMAN 1 Gerung. This research is a quasi experimental research with design called